Tracing the impact of the African Peer Review Mechanism on good governance and democracy in Ghana - Killander, Magnus (University of Pretoria, 2021)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa)) --University of Pretoria, 2021.